Pengembangan Kurikulum Pendidikan Agama Islam yang Responsif Gender: Menuju Kesetaraan dan Keadilan dalam Pendidikan - Oeky Diasworo; Nurfuadi (Jurnal Dirosah Islamiyah, 2024)
A responsive approach to gender issues in developing the Islamic religious education curriculum is becoming increasingly important because it supports efforts to achieve equality and justice in education. The aim of this study is to explore the urgency and implications of developing a gender-responsive curriculum in the context of Islamic religious education. Through in-depth analysis, this journal examines the concept of gender equality in Islamic education, identifies the challenges faced in integrating gender perspectives in the curriculum, and offers practical strategies to achieve this goal. A gender-responsive Islamic religious education curriculum must also pay attention to several things, namely: 1). Gender context: curriculum development must understand gender roles in society and recognize differences and equality between men and women. 2). Moral values: every lesson in the curriculum must include moral values that are relevant to religion, because they will help students understand not only the transfer of knowledge, but also character formation skills. 3). Competency-based curriculum: the use of a competency-based curriculum allows for a more holistic approach. Students not only gain knowledge, but also relevant skills and values. With this approach, it is hoped that the Islamic religious education curriculum can provide a more meaningful learning experience and support equality and justice in education.